ANALISIS HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN KEJADIAN STUNTING MENGGUNAKAN PENDEKATAN KUANTITATIF: STUDI LITERATUR REVIEW - Delima Delima; Firman Firman; Afdal Afdal (Universitas Fort De Kock, 2023)
The incidence of stunting in Indonesia is in the high category (24.4 percent), even though the WHO's maximum limit for stunting in a country is 20 percent. In West Sumatra at the end of 2021 it is 23%. The purpose of this study was to analyze the relationship between the mother's level of knowledge and the incidence of stunting using a quantitative approach. This research method uses a literature review study using articles in electronic databases, namely Google Scholar, Research Gate, and PubMed/Medline based on PRISMA (Preferred Reporting Items for Systematic Review & Meta Analysis). The search was carried out using the keywords